“Plusieurs fois je me sentis ému jusqu’aux larmes en l’écoutant”: Zur Improvisationskunst des Klavier- und Orgelspielers C.E.F. Weyse - Schwab, Heinrich W. (Danish Yearbook of Musicology, 2004)
‘Plusieurs fois je me sentis .mu jusqu’aux larmes en l’.coutant’ On the improvisational art of the pianist and organist C.E.F. Weyse During his visit to Copenhagen in 1841 the far-travelled ‘piano god’ Franz Liszt heard the organ played in the Copenhagen cathedral Vor Frue Kirke by a ‘M. Weyss’ and in the account he gave of his journey in Revue et Gazette Musicale de Paris of 19th September 1841 he confessed that he had several times been moved to tears by what he had experienced. With a point of departure in this richly faceted document, statements that permit us to form a more detailed impression of Weyse’s improvisational art are presented. According to Weyse himself – at the urging of Peter Grønland in 1789 – ‘several of my piano pieces arose in this fashion [i.e. through free imagination/improvisation]’. On the basis of the Fantasia in D major (‘comp. 1790’) which remained unprinted in Weyse’s lifetime, and the two concluding variations, Nos. 7 and 8, of the first movement of Piano Sonata No. 6 in Bb major (1799) a conception of a Weysian improvisation is inferred, as well as a number of technical details of his performance. Finally some consideration is given to the private and public significance of improvisation among the musicians of the period.